Nickel phosphate as a C-band optical pulse modulator - Ahmad, Harith; Yusoff, Norazriena; Monajemi, Hadieh; Reduan, Siti Aisyah (Springer, 2019)
This work discusses the fabrication of a nickel phosphate [Ni3(PO4)2]-polyvinyl alcohol (PVA) thin film and its application as an optical modulator for the generation of Q-switched pulses in the C-band region. A 50 cm long erbium-doped fiber with absorption coefficients of 250 dB/m and 16 dB/m at 980 nm and 1530 nm respectively was used as the gain medium. The modulation depth, saturable intensity and non-saturable loss were measured to be 56.43%, 0.15 kW/cm2 and 43.57%, respectively. Stable self-starting Q-switched pulses were observed at 1561.1 nm at an output power of 2.34 mW, a pulse width of 1.08 μs, and a repetition rate of 86.21 kHz, at the maximum pump power of 280.50 mW. The generated output was highly stable with a signal-to-noise ratio of 54.57 dB. The work undertaken has demonstrated the potential of Ni3(PO4)2 nanoparticles as an optically active material due to its excellent nonlinear saturable absorption characteristics, which translates to good laser performance. © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.